Pengaruh Video Edukasi terhadap Tingkat Pengetahuan Penderita Tuberkulosi tentang Penularan Tuberkulosis di Wilayah Kota Langsa - Ningsih, Nurhayati; Jurwita, Linda; Maulidya, Nurul; Dana, Bunga Novianty Sukma (Lembaga Teewan Journal Solutions, 2026)
Background: Tuberculosis (TB) remains a significant health challenge in Indonesia, including the Langsa City area. A primary obstacle in prevention efforts is the lack of understanding among patients regarding how the disease is transmitted. Effective education is essential to reduce the number of cases within the community. Objective: This study aims to analyze the effect of educational videos on the knowledge levels of TB patients concerning disease transmission in the Langsa City region. Methods: This is a quantitative study utilizing a quasi-experimental design with a Pretest-Posttest approach. The sample consisted of 20 respondents selected through total sampling. The intervention involved a 3-minute and 35-second educational video. Data analysis was performed using the Wilcoxon test. Results: The findings indicate a significant increase in knowledge among TB patients following the intervention. Prior to the intervention, most respondents' knowledge levels were categorized as fair or poor. Following the video education, the Wilcoxon test yielded a significance value of p=0.000 (p < 0.05), indicating a clear difference in knowledge before and after the intervention. Conclusion: The use of educational videos is effective in improving the knowledge of TB patients regarding disease transmission in Langsa City. It is recommended that healthcare professionals optimize the use of audiovisual media when providing health education to the public to ensure information is more easily understood.